The effect of precious metals in the NiAl coating on the oxidation resistance of the Inconel 713 superalloy - Zagula-Yavorska M.; Romanowska J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The rhodium incorporated aluminide coating was produced by the rhodium electroplating (0.5 μm thick layer) followed by the chemical vapor deposition process on the Inconel 713 superalloy. This coating is composed of the β-NiAl phase. A part of nickel atoms was replaced by rhodium atoms in the β-NiAl phase. The plain, rhodium and platinum incorporated aluminide coatings were oxidized at 1100 ºC under the atmospheric pressure. The oxidation kinetics of the rhodium and platinum incorporated aluminide coatings were similar, but different than oxidation kinetic of the plain coating. The α-Al2O3 was the main product both in rhodium and platinum modified coatings after 360 h of oxidation. Moreover, the γ-Ni3Al phase, besides the β-NiAl phase, was identified. The presence of 4 at. % rhodium in the coating provided similar oxidation resistance as the presence of 10-20 at. % platinum. Both rhodium and platinum incorporated aluminide coatings produced by the chemical vapor deposition process offer good oxidation protection of the Inconel 713 superalloy.